ANALISIS EFEKTIVITAS IKLAN MELALUI INSTAGRAM BOOKABUKU.COM SEBAGAI PERUSAHAAN START-UP BERBASIS PENDIDIKAN - dhia utamie ferza (Program Studi Manajemen Pembangunan Daerah. Fakultas Ekonomi dan Manajemen. IPB University, 2025)
ABSTRACT The enhancement of internet usage in Indonesia reflected by the strong interest of the society in using social media particularly Instagram in the daily life. Instagram is the most frequently used as the marketing tool by the business people. Bookabuku.com is one of the education-based start-up company in Indonesia. The objective of this research is to analyze the effectiveness of Bookabuku.com advertisements through Instagram. The data collected in this research is the primary data in form of online questionnaire, and the secondary data in the form of literature studies. The analytical method used are EPIC method and Direct Rating Method. According to EPIC, the value of EPIC rate is 3.27 which means the advertisements has been effective and has been able to introduce the services of Bookabuku.com. While based on DRM, the value of direct rating is 76.3 classified as a great advertisement which means having the ability to get attention, understanding, cognitive, affective and attitude in using the services of Bookabuku.com. Keywords: direct rating method, effectiveness of advertising, EPIC method, start-up.